2000
DOI: 10.1096/fj.00-0370fje
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide binds to the CaLB domain of cytosolic phospholipase A2and facilitates its membrane docking and arachidonic acid release

Abstract: Excessive production of eicosanoids is characteristic of many inflammatory diseases. In this study we show that ceramide, which is an early messenger of inflammatory cytokine action, exerts a dual effect on the cytosolic phospholipase A2 (cPLA2), the rate-limiting enzyme in arachidonic acid release and subsequent eicosanoid formation. Stimulation of renal mesangial cells with exogenous short-chain ceramide analogs for 30 and 60 min leads to a concentration-dependent increase in arachidonic acid release that is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(81 citation statements)
references
References 48 publications
2
77
0
2
Order By: Relevance
“…9B. These increases were in the 3-6-fold range, much like those previously reported for PI-4,5-P 2 addition in the small unilamellar vesicle substrate systems (33,55). This 3-6-fold increase is in contrast to the Lyso-PC/Triton X-100 mixed micelle system that gave greater than a 100-fold increase in activity in the presence of 1 mol % PI-4,5-P 2 (Fig.…”
Section: Casupporting
confidence: 84%
See 1 more Smart Citation
“…9B. These increases were in the 3-6-fold range, much like those previously reported for PI-4,5-P 2 addition in the small unilamellar vesicle substrate systems (33,55). This 3-6-fold increase is in contrast to the Lyso-PC/Triton X-100 mixed micelle system that gave greater than a 100-fold increase in activity in the presence of 1 mol % PI-4,5-P 2 (Fig.…”
Section: Casupporting
confidence: 84%
“…Several others reports have shown that PIP n s, including PI-4,5-P 2 , enhance the activity of GIVAPLA 2 by less than 10-fold (21,22,33,55). At first glance, this seems to contradict our reports that PI-4,5-P 2 enhances the activity of GIVAPLA 2 in large unilamellar vesicles composed of PAPC by 20-fold (1 mol %) or 55-fold (3 mol %) and in PAPC/Triton X-100 mixed micelles by up to 120-fold (1 mol %) (23).…”
Section: Camentioning
confidence: 92%
“…2B). In this setting, cPLA 2 is translocated to the membrane in a Ca 2+ -independent fashion by increased membrane affinity and enhanced specific activity that has been linked to generation of PIP 2 and conformational changes (5,(31)(32)(33), as well as generation of C1P (34), ceramide (35), and diacylglycerol (36). Additionally, sPLA 2 is reported to significantly contribute to prostaglandin production during late-phase activation, but not during 10-min calcium ionophore-induced metabolism (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ceramide has been shown to directly regulate several molecules including cathepsin D [53], phospholipase A 2 [54], kinase suppressor of Ras [55], ceramide-activated protein serine-threonine phosphatases (CAPP) [56] and protein kinase C isoforms [57, 58]. Further, ceramide has been shown to regulate the activity of the potassium channel Kv1.3 and calcium release-activated calcium (CRAC) channels [59-60].…”
Section: Ceramidementioning
confidence: 99%